Assessment of the effect of personality type of architects and non-architects on the choice of facade style in residential buildings - Mahsa Moazeni; Neda Ziabakhsh (طراحی و برنامه ریزی در معماری و شهرسازی)
Generally, the description of architects and non-architects of a building is different. The differences are important because they can often lead to a severe mismatch between the preferences of architects and non-architects. In order to establish the best possible communication between architecture and humans, looking at architecture from a psychological perspective - especially personality psychology - has become increasingly important. In order to achieve this goal, and considering that part of the architect's work is understanding the preferences and perceptions of the customer, understanding the perspective and better understanding the demands of humans is necessary. This article attempts to establish a meaningful relationship between personality type and architectural preferences using a combination of two tests. To identify the personality type, the DISC behavioral model was used for the test subjects; then, using a selective preference test, 12 images of residential facades were selected and the images were black and white to eliminate the color factor on the individual's preferences. The images were divided into two groups of villas and apartments, and 78 test subjects were asked to prioritize the images. The test subjects were divided into two groups of architects and non-architects. SPSS software was used to analyze and interpret the results of the tests and the impact of the individual's personality type on their choices. The research results show that all female architects chose the minimal and modern style as their first priority. The traditional and modern-traditional styles were among the preferred styles among male architects with personality type C, and the classic style as the first choice in personality type S with a frequency of 100% and 66.7%, indicating a significant relationship between personality type and individual preferences. The modern and minimal style had a higher frequency percentage as the first priority in all personality types, both in the architects' group and in ordinary individuals. The classic style had the highest frequency as the last priority, and simplicity, beauty, and modernity were the most used descriptions in the choices.